The INFLUENCE OF HEDONIC VALUE AND CUSTOMER EXPERIENCE ON CONSUMER DECISION-MAKING: A STUDY OF FOREIGN BRAN RETAIL IN INDONESIA WITH CUSTOMER SATISFACTION AS MEDIATION - Elzagi, Verliana; Laulita, Nasar Buntu (Journal of Business Studies and Management Review, 2024)
This study aims to fill the gap in the literature by exploring how hedonic value and customer experience influence consumen decision-making in foreign bran retail in Indonesia, with particular focus on the mediating role of customer satisfaction. This study consists of two independent variables, namely hedonic value and brand experience and one dependent variable, namely consumer decision-making and customer satisfaction as a mediating variable. The method used is quantitative where research data collection using questionnaires filled out by community respondents throughout Indonesia. The research results obtained are: a) There is a significant influence between hedonic value on brand satisfaction, b) there is a significant influence between hedonic value on consumer decision-making, c) there is a significant influence between brand experience on customer satisfaction, d) there is a significant influence between brand experience on consumer decision-making, e) there is no significant influence between customer satisfaction on consumer decision-making, f) customer satisfaction cannot mediate the effect of hedonic value on consumer decision-making, g) customer satisfaction cannot mediate the effect of brand experience on consumer decision-making.